Incident dementia in kidney transplantation recipients: a matched comparative nationwide cohort study in South Korea - Baek, Seon Ha; Park, Jina; Park, Sehoon; Yu, Mi-Yeon; Kim, Ji Eun; Park, Sang Hyun; Han, Kyungdo; Kim, Yong Chul; Kim, Dong Ki; Joo, Kwon Wook; Kim, Yon Su; Lee, Hajeong (Kidney research and clinical practice, 2023)
Recent studies have shown that patients with end-stage renal disease (ESRD) are at elevated risk of dementia. However, whether kidney transplantation (KT) lowers the risk for incident dementia remains unclear. From the Korean National Health Insurance Service database, we identified incident KT recipients aged ≥40 years without any history of dementia between 2007 and 2015. We also established a pair of age-, sex-, and inclusion year-matched control cohorts of patients with incident dialysis-dependent ESRD and members of the general population (GP) without a history of dementia, respectively. Cases of incident all-cause dementia, including Alzheimer disease (AD), vascular dementia (VD), and other kinds of dementia, were obtained from baseline until December 31, 2017. We followed 8,841 KT recipients, dialysis-dependent ESRD patients, and GP individuals for 48,371, 28,649, and 49,149 patient- years, respectively. Their mean age was 52.5 years, and 60.6% were male. Over the observation period, 55/43/19 KT recipients, 230/188/75 dialysis-dependent ESRD patients, and 38/32/14 GP individuals developed all-cause dementia/AD/VD. The risks of incident all-cause dementia, AD, and VD in KT recipients were similar to those in GP (hazard ratio: 0.74 [p = 0.20], 0.74 [p = 0.24], and 0.59 [p = 0.18], respectively) and significantly lower than those in dialysis-dependent ESRD patients (hazard ratio: 0.17 [p < 0.001], 0.16 [p < 0.001], and 0.16 [p < 0.001], respectively). Older age and diabetes mellitus at the time of KT were risk factors for incident all-cause dementia and AD in KT recipients. This is the first study to show a beneficial impact of KT on incident dementia compared to dialysis dependency.